Remembrance of things practiced with fast and slow learning in cortical and subcortical pathways - James M. Murray (Nature Portfolio, 2020)
Surprisingly, motor cortex becomes less involved in performing skilled motor behaviors as they are practiced. This is addressed by a model of two descending pathways featuring different types of learning: fast learning in a cortical pathway to maximize rewards and slow learning in a subcortical pathway to reinforce behaviors through repetition.